Synthesis and structural and thermal properties of cyclotriphosphazene-based ionic liquids: tribological behavior and OFET application - Destegul, Ali; Akbas, Huseyin; Karadag, Ahmet; Canimkurbey, Betul; Yerli, Yusuf; Tekin, Kadir Cihan; Malayoglu, Ugur; Kilic, Zeynel (SPRINGER HEIDELBERG, 2019)
Three new fully substituted starting materials (Pz1-3) were synthesized reacting dimethylaminoethanol, 3-dimethylamino-1-propanol, and 4-pyrridinemethanol, which were saltified using metallic sodium, with partly substituted phosphazene (Pz) compound. Phosphazene-based ionic liquids (PzILs), PzIL1-3, were obtained from the reaction of the starting materials with CH3I. New ionic liquids (PzIL1a-3a) were obtained by replacing the I- ions of these ionic liquids with the NTf2- anions. The structures of PzILs were elucidated by elemental analysis, FTIR, and H-1, C-13 {H-1}, and P-31 {H-1} NMR techniques. The thermal properties of all compounds were investigated using thermogravimetric (TG) analysis. Compared with the output materials, the thermal stability of the ionic liquids was found to be higher, 160, 199, and 228 degrees C for PzIL1-3 respectively, and 270, 204, and 287 degrees C for PzIL1a-3a respectively. At the same time, the viscosity measurements of PzIL1a-3a compounds obtained as liquids in room temperature were measured with a cone/plate viscometer. It is understood from the viscosity values that the fluidities of these compounds are as low as 864, 3801, and 423,700cP, respectively (water viscosity is 0.7977cP at 30 degrees C). In addition to these studies, sliding wear test was conducted at room temperature using AA7075 disc specimen against the stationary 100Cr6 steel ball. The wear protection of PzILs was determined considering the volume loss of AA7075.
Keywords: Phosphazene; Phosphazene-based ionic liquid; Tribology; Organic field-effect transistor; DNA INTERACTIONS; ANTIMICROBIAL ACTIVITIES; CYTOTOXIC ACTIVITIES; TEMPERATURE; PERFORMANCE; CYCLOPHOSPHAZENE; LUBRICATION; DERIVATIVES; ADDITIVES; Chemistry; Electrochemistry; Physics